Increasing the Activity of Grade VII Students Through the Cooperative Learning Model of Invasion Game Materials at SMPN 8 Banjarbaru - Setiawan, Yoga Rudi; Rakhman, Arie; Putra, Trinaldi Andika (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This research is motivated by the low activity of students in learning Physical Education, Sports, and Health (PJOK) in grade VII students of SMPN 8 Banjarbaru which can be seen from the lack of participation, cooperation, courage, and enthusiasm of students during the learning process. Although cooperative learning and play-based approaches have been widely used in physical education, limited classroom action research is still examining how modified invasion play can support increased student activity, cooperation, courage, and enthusiasm in grade VII PJOK learning. This study aims to describe the increase in student activities through the application of the invasion game-based cooperative learning model. The type of research used is Classroom Action Research (PTK) with 32 research subjects of grade VII SMPN 8 Banjarbaru. The sampling technique uses total sampling. The research instrument is in the form of student activity observation sheets which are compiled based on indicators of student participation, cooperation, courage, and enthusiasm. Data collection techniques are carried out through observation and documentation, while data analysis uses quantitative and qualitative descriptive analysis. The results of the study showed a gradual increase in student activity, namely by 57% in the pre-test stage with the sufficient category, increased to 72% in the first cycle with the good category, and reached 85% in the second cycle with the very good category. The findings of the study show that the application of cooperative learning through invasion games supports the improvement of student activities in the observed classroom context. Thus, this learning model can be used as an alternative learning strategy to support the quality of the PJOK learning process.